Transcriptome-wide N6-Methyladenosine Methylome Profiling Reveals m6A Regulation of Skeletal Myoblast Differentiation in Cattle (Bos taurus) - Yang, Xinran; Wang, Jianfang; Ma, Xinhao; Du, Jiawei; Mei, Chugang; Zan, Linsen (Frontiers in Cell and Developmental Biology, 2021)
N6-methyladenosine (m6A) is the most prevalent methylation modification of eukaryotic mRNA, and it plays an important role in regulating gene expression. Previous studies have found that m6A methylation plays a role in mammalian skeletal muscle development. However, the effect of m6A on bovine skeletal myogenesis are still unclear. Here, we selected proliferating myoblasts (GM) and differentiated myotubes (on the 4th day of differentiation, DM) for m6A-seq and RNA-seq to explore the m6A methylation modification pattern during bovine skeletal myogenesis. m6A-seq analysis revealed that m6A methylation was an abundant modification of the mRNA in bovine myoblasts and myotubes. We scanned 5691-8094 m6A-modified transcripts, including 1437 differentially methylated genes (DMGs). GO and KEGG analyses revealed that DMGs were primarily involved in transcriptional regulation and RNA metabolism, as well as insulin resistance and metabolic pathways related to muscle development. The combined analysis further identified 268 genes that had significant changes at both m6A and mRNA levels, suggesting that m6A modification may regulate myoblast differentiation by mediating the expression of these genes. Furthermore, we experimentally confirmed four genes related to myogenesis, including MYOZ2, TWIST1, KLF5 and MYOD1, with differential changes in both m6A and mRNA levels during bovine myoblast differentiation, indicating that they can be potential candidate targets for m6A regulation of skeletal myogenesis. Our results may provide new insight into molecular genetics and breeding of beef cattle, and provide a reference for investigating the mechanism of m6A regulating skeletal muscle development.